UNIVERSITY GENRES IN DISCIPLINARY DOMAINS: SOCIAL SCIENCES AND HUMANITIES AND BASIC SCIENCES AND ENGINEERING - Parodi, Giovanni (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2009)
The issue of disciplinarity is becoming increasingly salient in discourse studies. Questions of how differences in the structures of intellectual fields and curricula help shape educational experiences and outcomes are the focus of studies across a variety of disciplines using a range of approaches. One way to access the specialized written genres employed by academia is to begin from the tenet that all materials read by students during their university training reveal relevant data about disciplinary genres. This article presents research that focuses on the collection, construction, and description of an academic corpus based on texts collected in four disciplinary domains of knowledge: Industrial Chemistry, Construction Engineering, Social Work, and Psychology. A review of the concepts of genre and academic discourse is presented. This is followed by a description of the procedures of collecting and organizing the Academic Corpus PUCV-2006, which comprises almost 60 million words. In addition, a preliminary genre typology of the 491 text corpus is provided.